ANALISIS PROFITABILITAS USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) AMANAH MANDIRI KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI PEKANBARU - Ryan Pahlawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: The Savings and Loans Village Economic Business (UEK-SP) plays a very important role in supporting the economic development of the community at the village level. Therefore, good processing of UEK SP is needed, in order to survive and continue to serve the needs of the community. The purpose of this study was to analyze the profitability of the Savings and Loans (UEK-SP) Amanah Mandiri Village, East Sidomulyo Village, Marpoyan Damai District, Pekanbaru. In this study using descriptive analysis by analyzing financial ratios such as working capital turnover ratios and profitability ratios. The results showed that the management of working capital in the savings and loan unit was better than that of the sub-district economic enterprise (UEK). However, the limited working capital of the savings and loan business unit requires the sub-district government to increase the working capital of the savings and loan unit, for example by setting aside profits from the UEK to increase the working capital of the savings and loan unit. Thus, the savings and loan unit can increase its profitability.Keywords: Profitability, Economic Business Of Save And Loan Sub-District (UK-SP)